The Potential Of Natural Resources As Agrotourism In North Sumatera: A Pathway To Community Empowerment - Ilvira, Rika Fitri; Arumugam, Nalini (Universitas Medan Area, 2024)
In the realm of sustainable agriculture and rural development, agrotourism emerges as a promising avenue for economic growth and community empowerment. This study delves into the potential of agrotourism in North Sumatra, particularly focusing on its physical and non-physical attributes as well as community-based empowerment strategies. The background elucidates the global rise of agritainment activities and the growing significance of agrotourism in Asian countries. Despite the prevalence of agrotourism in Indonesia, North Sumatra has yet to fully harness its potential, with limited development observed in the region. To address this gap, the study employs a mixed-methods approach, utilizing quantitative methods to quantify physical and non-physical potentials, followed by qualitative analysis to explore community-based agrotourism potential. The findings underscore North Sumatra's abundant natural resources, diverse agricultural commodities, and existing social institutions as key drivers for agrotourism development. Moreover, the study highlights the importance of community participation and empowerment in fostering sustainable agrotourism practices. By leveraging these potentials and fostering community engagement, North Sumatra can pave the way for inclusive economic growth, tourism enhancement, and community development. This research contributes to the understanding of agrotourism development strategies and holds implications for sustainable rural development globally.